2004
DOI: 10.1021/bi0300985
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Structure of Telomeric DNA Sequences Forming Quadruplexes Containing Four G-Tetrads with Different Topological Arrangements

Abstract: Telomeres are DNA-protein structures at the ends of eukaryotic chromosomes, the DNA of which comprise noncoding repeats of guanine-rich sequences. Telomeric DNA plays a fundamental role in protecting the cell from recombination and degradation. Telomeric sequences can form quadruplex structures stabilized by guanine quartets. These structures can be constructed from one, two, or four oligonucleotidic strands. Here, we report the thermodynamic characterization of the stability, analyzed by differential scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 47 publications
10
58
0
Order By: Relevance
“…In addition we can notice the emergence of an absorption at 920 cm -1 which may reflect the existence of guanosines in syn conformation. Such a band had been previously observed in the left-handed Z form spectra and is probably related to a C-N vibration in syn guanosines [44]. .…”
Section: Ftir Characterization Of Tetraplexes : Interpretation Of Vibsupporting
confidence: 61%
“…In addition we can notice the emergence of an absorption at 920 cm -1 which may reflect the existence of guanosines in syn conformation. Such a band had been previously observed in the left-handed Z form spectra and is probably related to a C-N vibration in syn guanosines [44]. .…”
Section: Ftir Characterization Of Tetraplexes : Interpretation Of Vibsupporting
confidence: 61%
“…These spectra are consistent with the parallel-stranded quadruplex structures. 17,35 The spectrum of the LNA sequence presents an additional positive band at 288 nm, and this unusual band can be associated with the presence of the quadruplex structure. 25 We found that the melting and annealing curves for all the sequences show hystheresis.…”
Section: Thermodynamics Of Quadruplexes Dissociationmentioning
confidence: 99%
“…In G-tetrad, the Guanine bases are linked through Hoogsteen pairing or by bifurcated hydrogen bonds between N1-H, N2-H, and O6 atoms as reported in [23][24][25][26][27][28][50][51][52]. Guanine tetrad is formed between the donor and acceptor atoms (see Fig.…”
Section: Resultsmentioning
confidence: 96%